Ophelia's terror: Anatomising the figure of the female suicide bomber in The Al-Hamlet Summit. Issue 1 (July 2019) - Walkling, Saffron Vickers
2002: three months, three Palestinian women, three bombs. That same year, Sulayman Al-Bassam premiered The Al-Hamlet Summit, his political appropriation of Hamlet, Mahmoud Darwish's Palestinian poetry, and Heiner Müller's Hamletmachine, at the Edinburgh Fringe Festival. Mapping the politics of anger and despair onto Shakespeare's play, he suggests that terrorism from Palestine to the United States is rooted in colonialism and Western military interventions in the Middle East. Hamlet is a jihadist, Horatio becomes a British Arms Dealer and Ophelia, a suicide bomber. This article explores the politics of representation in the body of Ophelia, who is anatomised as she detonates herself under the palace orange trees.